Moksartham jagaddhita - Mantra, I. B., 1928-; Nala, Ngurah, 1936- (Denpasar, Bali : Upada Sastra, 1995)
Balinese Hinduism's views on economic development, human ecology; papers of seminars.
PRIORITY 3.
Includes bibliographical references.
In Indonesian.
Keywords: Hinduism -- Indonesia -- Bali Island